PERAN AUDIT INTERNAL DALAM MENDORONG EFEKTIVITAS SISTEM PENGENDALIAN INTERN PEMERINTAH DAERAH (STUDI EMPIRIS PADA INSPEKTORAT DI PROVINSI MALUKU) - Muhammad Fadila Laitupa; Theresia Febiengry Sitanala; Dirk Berly Tehuayo (Soso-Q : Jurnal Manajemen, 2021)
AbstractThis study aims to examine the role of internal audit on the government's internalcontrol system. The population of this study were auditors and employees of the MalukuProvince Inspectorate. The sample in this study were 84 auditors and employees of theMaluku Province Inspectorate who had audited. The results of the study stated thatthere was a positive and significant influence between the role of internal audit and theeffectiveness of the internal control system in Maluku Province. This states that theinternal audit carried out by the auditors of the inspectorate spread over four districtsand cities as well as the auditors of the inspectorate of Maluku province has performedits role as a leader who is the forefront of the funnel by coordinating, carrying outcontrol functions, encouraging the creation of bureaucratic reform and goodgovernance.Keywords: Internal Audit, Government Internal Control System